Are urban landscapes associated with reported life satisfaction and inequalities in life satisfaction at the city level? A cross-sectional study of 66 European cities. (April 2019) - Olsen, Jonathan R.; Nicholls, Natalie; Mitchell, Richard
Abstract: With more than half the world's population residing in urban areas and this proportion rising, it is important to understand how well-planned urban environments might improve, and reduce inequalities in, quality of life (QoL). Although studies suggest city-level characteristics hold independent influence on QoL, they generally lack a theoretically informed approach to understanding how the whole city landscape might be implicated, have paid scant attention to inequalities in QoL and often focus on small numbers of cities or countries. We applied theory and methods from landscape ecology to explore associations between cities' land cover/use, residents' reported life satisfaction and within-city socio-economic inequalities in life satisfaction. We joined individual-level responses to the European Urban Audit (EUA) Perception Surveys (2012, 2015) with city-level data from the European Urban Atlas classifying land cover/use into 26 different classes. Our sample included 63, 554 people from 66 cities in 28 countries. Multilevel binary logistic models found that specific land use measures were associated with life satisfaction, including the amount of a city which was: residential (OR:0.991, 95%CI 0.984–0.997); isolated structures (OR:1.046, 95 CI 1.002–1.091); roads (OR:0.989, 95%CI 0.982–0.996); pastures (OR: 1.002, 95% CI 1.002–1.003) and herbaceous vegetation (OR:0.998, 95%CI 0.997–0.100). A more even distribution of land cover/use (β: 1.561, 95%CI -3.021 to −0.102) was associated with lower inequality in life satisfaction. This is the first study to theorise and examine how the entire urban landscape may affect levels of and inequalities in wellbeing in a large international sample. Our finding that more equal distribution of land cover/use is associated with lower levels of socio-economic inequality in life satisfaction supports the idea that city environments could be equigenic – that is, could create equality. Our findings can aid urban planners to develop and build cities that can contribute to improving, and narrowing inequalities in, residents' life satisfaction. Highlights: It is important to understand how urban environments might improve quality of life. We explored associations between land covers and life satisfaction. We also explored within-city socio-economic inequalities in life satisfaction. Specific land use measures were associated with life satisfaction. Land cover evenness was associated with lower inequality in life satisfaction.